Short-term adverse effects of the apolipoprotein E ϵ4 allele over language function and executive function in healthy older adults - Li W (Dove Medical Press, 2019)
Wei Li,1,2,* Qi Qiu,1,2,* Lin Sun,1,2,* Xia Li1,2 Shifu Xiao1,21Department of Geriatric Psychiatry, Shanghai Mental Health Center, Shanghai Jiao Tong University School of Medicine, Shanghai, China; 2Alzheimer’s Disease and Related Disorders Center, Shanghai Jiao Tong University, Shanghai, China*These authors contributed equally to this workBackground: The 4 allele of the apolipoprotein E (APOE) gene is known as a risk factor for cognitive impairment. How APOE ϵ polymorphism affects the language and executive functions of healthy aging subjects remains less clear.Purpose: In this follow-up study, the relationship between APOE status and cognitive performance across various cognitive domains in healthy individuals (without dementia or mild cognitive impairment (MCI)) over 60 years old was investigated.Patients and methods: Based on multiplex amplification refractory mutation system polymerase chain reaction (PCR), 228 subjects (n=228; mean age: 70.59±8.07 years old; male %=40.8%) were divided into three groups, e2 (ϵ2/ϵ2 and ϵ2/ϵ3, n=35), e3 (ϵ3/ϵ3, n=152), and e4 (ϵ2/ϵ4, ϵ3/ϵ4, and ϵ4/ϵ4, n=41).Results: There was no statistical difference (p>0.05) in the general demographic data and neuropsychological tests among the three groups on the baseline; however, e4 group showed a greater drop rate (p<0.05) versus non-carriers on verbal fluency (e2: −0.043±0.221; e3: -0.081±0.239; e4: 0.069±0.329) and Webster picture completion (e2: 0.055±0.281; e3: 0.083±0.428; e4: 0.438±1.280) over the subsequent one year.Conclusion: The findings suggest that possession of the APOE ϵ4 allele predicted a higher decline on tasks of language function and executive function in healthy elderly. And further research is required to determine whether strengthening the training of language function and executive function will delay the occurrence of cognitive impairment.Keywords: APOE, language function, executive function, healthy elderly